Knowledge and attitudes of libyan dental students about HIV/AIDS infection and HIV-positive patients - Syed Wali Peeran; P G Naveen Kumar; Karthikeyan Ramalingam; Syed Ali Peeran; Nureldeen Abdel Jawad N Elhammali; Ahmed Elhassan; Fatma Mojtaba Alsaid (Wolters Kluwer Medknow Publications, 2015)
Introduction: Though the possibility of contracting infection from human immuno-deficiency virus (HIV) infected patient is very slim, dental professionals show high reluctance to treat such patients. Their attitude and behavior is a reflection of their understanding about the disease. Aim: The aim of the survey was to evaluate the knowledge and attitude of dental students toward HIV/acquired immuno-deficiency syndrome (AIDS), oral indicators, ethical aspects of its treatment, and their inclination to treat HIV/AIDS patients. This is the first attempt of such evaluation among Libyan students to the best of our knowledge. Materials and Methods: The study was conducted as a cross-sectional survey using a questionnaire among 101 dental students comprising 3 rd year, the final year and BDS interns in Faculty of Dentistry, Sebha University, Sebha, Libya. The results were analyzed for statistical significance using SPSS version 17.0 (SPSS Inc., Chicago, IL, USA). Results and Discussion: The response rate to the questionnaire was 100%. Statistical significant correlations were observed in attitudes toward the curriculum, modes of transmission, treatment of HIV-infected patient, information of HIV status to patients, rights to reject treatment of infected patients, stress on treating and resuscitation of such patients. Conclusion: Our study reflects the knowledge status and positive attitude of Libyan students toward management of HIV. Sincere efforts should be made to improve the modes of educating the students about the HIV infection and its dental implications.